Study of subclinical hypothyroidism in elderly and its correlation with lipid profile - Mohanty, Namita; Parhi, Satyajit (International Journal of Research in Medical Sciences, 2020)
Background: Although hypothyroidism accompanying dyslipidemia previously recognized as important risk factor for cardiovascular disease, but now subclinical hypothyroidism emerged as important risk factor for atherosclerosis and myocardial infarction especially in elderly people. Subclinical Hypothyroidism (SCH) is a state characterized by normal serum T3 and T4 level with elevated TSH level having minimal signs and symptoms. There are limited studies on SCH and dyslipidemia in elderly people in India, so this study was undertaken to correlate thyroid function abnormality with lipid profile in elderly population. Methods: This observational study was conducted in 74 elderly people more than 60 years age group having symptoms of SCH i.e. fatigue, weakness mild thyroid swelling, weight gain etc. who did not previously have a diagnosis of hypothyroidism, diabetes mellitus, previous thyroidectomy, renal failure, hepatic failure, systemic hypertension etc. They had normal T3, T4 level and raised TSH value. Cases with TSH value >5 mIU/L but normal T3, T4 level were evaluated further for lipid profile. Results: Elderly females suffered more from SCH in the age group of 60-70 years. Participants with SCH had significantly higher cholesterol (p value=0.0216), higher LDL (p value=0.0241) and higher triglyceride (p value =0.0004) with increasing TSH showing positive correlation. There is no significant correlation between decreasing HDL and TSH value. Conclusions: All elderly people should be routinely screened for thyroid function abnormality. Those have SCH should also be evaluated for dyslipidemia so that they can be treated with lipid lowering drugs and low dose thyroxine judiciously to prevent atherosclerosis.